Cartera vencida en el Centro Comunal Cristo Del Consuelo de la ciudad de Babahoyo en el periodo de 2023. - Gaibor Gavilánez, Sandy Julady (2024)
This study focuses on examining the outstanding portfolio at the Christ of Consolation Community Centre in the city of Babahoyo in the period 2023. The problem addressed relates to customer defaults, which could have a negative long-term financial impact. The justification for this study lies in the need to properly manage the outstanding portfolio in order to ensure the financial and operational stability of the organization. Objectives include identifying the causes or reasons for the outstanding portfolio, analysing the portfolio recovery processes and calculating the liquidity index to be able to determine whether it covers its short-term obligations. This study was carried out under the methodology of mixed approach, descriptive method, deductive and research instrument. In conclusion, it emphasizes the implementation of a tracking and reminder system for outstanding clients, establishing clear collection policies, improving the credit assessment process and training staff in the management of outstanding portfolios. The need for further strengthening of financial management is emphasized in order to reduce any future risk.